Imidazolium-based ionic liquid type dependence of the bending response of polymer actuators - Mejri, R., (2016)
Actuators based on polymer blends of poly(vinylidene fluoride) (PVDF) with 40 % of different ionic liquids (IL) are prepared by solvent casting. [C2mim][Cl], [C6mim][Cl], [C10mim][Cl], [C2mim][NTf2], [C6mim][NTf2] and [C10mim][NTf2] were selected in order to evaluate the effect of anion and cation sizes in the bending properties. The microstructure, mechanical and electrical properties of the blend depend on the IL type, which in turn leads to a different bending response. In particular, the mechanical properties are independent on the IL type but the AC conductivity of the composites depend more on the anion type than on the size of the alkyl chain connected to the imidazolium based cation. Thus, the bending response of the IL/PVDF composites is correlated with the anion and cation sizes and a maximum bending response of 0.3 % is achieved for a 10 volts square signal in the IL/PVDF composite with 40 wt% content of [C2mim][NTf2].